posted by .

P(x) = 3x^3 - 7x^2 - 4x + 2

P(1 + √ 3) =

## Similar Questions

1. ### Algebra

How would i complete these problems? 1. (√6mn)^5 2. ^3√16x - ^3√2x^4 3.^4√x • ^3√2x 4. ^3√72x^8 5. √63a^5b • √27a^6b^4 and are these problems correct?
2. ### Math

Find an equation of the line that bisects the obtuse angles formed by the lines with equations 3x-y=1 and x+y=-2. a. (3√2 +√10)x-(√10 + √2)y-2√10+√2=0 b. (3√2 - √10)x+(√10 - √2)y+2√10+√2=0 …

Identify the domain and range: 1.) y = x^2 / 4x^2 - 1 2.) y = -3 / (x+2)^2 + 1 3.) y = ³√-x^2

i need help with this quretsion ; i don't know if im right, and i dontknwo what do next question expand and simplfy: 4√7(2√3 + 3√6 - √7) my work = 8√21 + 12√42 -4√49 please help me

i need help with this quretsion ; i don't know if im right, and i dontknwo what do next question expand and simplfy: 4√7(2√3 + 3√6 - √7) my work = 8√21 + 12√42 -4√49 please help me

I don't get how to do this. I'm so lost please help me. Determine the equation of the parabola with roots 2+√3 and 2-√3, and is passing through the point (2,5) this is what i did but its the wrong answer: y= a[x + (2+√3)] …
7. ### maths

I will be thankfull to you if you help me to solve the below problem: 6√x-11/3√x=2√x+1/√x+6 I tried to solve the above problem like this: (6√x-11)(√x+6)=(3√x)(2√x+1) 6√x(√x+6)-11(√x+6)=(3√x)(2√x)+(3√x)(1) …